A Scoping Review of Interventions to Promote Diversity, Equity, and Inclusion in the United States Healthcare Workforce - Katherine A. Hill; Andrew W. Austin; Felicity T. Enders (Journal of Medical Education and Curricular Development)
Background Diversifying the healthcare workforce is critical to achieving a healthier, more equitable society. Objectives The objective of this literature review was to examine and synthesize the literature on interventions to promote diversity, equity, and inclusion (DEI) in people who are currently enrolled in the workforce or in a terminal degree/training program and who are located in the following institution types: medical centers; healthcare organizations; and schools of dentistry, medicine, nursing, nurse practitioners, physician assistants, and public health. Methods A literature search was performed on November 2, 2023 in Ovid MEDLINE ® . We reviewed titles and abstracts of all retrieved articles from 2000 forward and the full text of articles included in the final review. We included English-language articles published in peer-reviewed journals that detailed 1 or more interventions to promote DEI in the United States and United States territories. All data included in the final review was extracted by a single investigator and charted using an Excel spreadsheet. Results The authors identified 55 articles for inclusion, 4 of which aggregated and analyzed data from many interventions. The remainder detailed 52 interventions across 25 states and Puerto Rico. Most articles did not include a comparison group (38, 69%). The types of interventions identified were: institutional change (14, 27%), mentorship (13, 25%), development programs (13, 25%), pathway programs (5, 10%), financial support (2, 4%), and workshops (2, 4%). Three (6%) interventions could not be categorized. Most studies detailed interventions in medicine (28, 54%) and nursing (11, 21%), focused on racial and ethnic (42, 81%) and/or sex (12, 23%) diversity, and targeted students (33, 64%) and/or faculty/staff (28, 54%). Conclusion Many different types of interventions have been trialed to promote workforce DEI in the United States healthcare workforce. These efforts must continue to achieve a diverse and equitable healthcare workforce.